A V-Cycle Multigrid Method for the Plate Bending Problem Discretized by Nonconforming Finite Elements (Journal of Computational Mathematics, 1999)
In this paper, an optimal V-cycle multigrid algorithm for some famous nonconforming plate elements is established.
Keywords: The pate problem; V-cycle multigrid; Nonconforming elements.